Production of handicrafts, wares and novelty items from coconut wood, fronds and coconut fruit residues - Luisito J. Penamora (International Coconut Community Journal, 2007)
The production of handicrafts, wares and novelty items utilizing small and short pieces of coconut wood, fronds and shell is a highly feasible and viable option to derive income from coconut residues and other cellulosic materials found in coconut plantation. Handicrafts and novelty items from coconut fronds, wood and other residues are potential export commodities that can compete with other indigenous products because of their unique appearance and quality. Given the tremendous amount of readily available raw materials from coconut farms, a manufacturer is assured of a sustainable operation. Property tests conducted on coconut frond’s structure have shown its fitness to be used as alternative material to some light wood species. It has an average specific gravity (sg) value of 0.20 and mean volumetric shrinkage of 63%. Effectual use investigations of coconut fronds and coconut fruit residues on machining, treatment, gluing properties and finishing requirements are all satisfactory. With the use of a technique, “mix and match”, they can be skillfully combined with coconut wood to make good finished products. Skills, creativity and craftsmanship on the part of the people involved in the job were crucial aspects of the production. Some of the crafts and novelty items produced were; all-purpose trays, trophies, flower vases and candle holders, chairs, dividers, plant boxes, table and dresser to name a few. The production cost estimates was at minimum with about 50-60 percent cheaper than the traditional materials such as wood.